THE ATTITUDE OF YOUNG PEOPLE IN BOSNIA AND HERZEGOVINA TOWARDS DIGITAL CONTENT - BETWEEN VIRTUAL AND REAL REALITY - Trninic, Dragana; Kuprešanin Vukelić, Anđela (Politeia, 2025)
Young people in Bosnia and Herzegovina (BiH), members of Generation Z, most often get their information through digital media, i.e. social networks, mostly choosing entertaining, interesting and humorous content. Social networks are their first choice for information and they spend most of their free time with them. The focus of the paper is on digital media content that young people often use. The aim of the paper is to identify specific internet portals, social network accounts, influential individuals or groups that young people follow and whose content they consume the most. The results collected using the survey method using an online questionnaire indicate that young people in BiH visit the following internet portals the most: Nezavisne.com, Klix.ba, Rtrs.tv, while on social networks they most often follow the accounts of influencers and celebrities. Also, most young people do not distinguish between internet portals and social network accounts. Their favorite influencers or YouTubers are: Zorana Jovanović, Anja Blagojević, Adriana Džehverović and Baka Prase. It is concluded that young people in BaH do not often use digital media and social networks in a productive way and that they lack adequate media and information literacy skills to use the capacity of digital media for education, personal development, assistance in learning or navigating everyday life.